Disposable polymeric electromagnetic actuated micropump - Chee, Pei Song; Rashidah, Arsat, Dr.; Uda, Hashim, Prof. Dr.; Ruzairi, Abdul Rahim, Prof. Dr.; Leow, Pei Ling (American Scientific Publishers, 2013)
Link to publisher's homepage at http://www.aspbs.com/